2011
DOI: 10.5535/arm.2011.35.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dominant Versus Non-dominant Vision in Postural Control

Abstract: ObjectiveTo assess the effect of dominant and non-dominant vision in controlling posture in quiet stance.MethodTwenty-five healthy elderly subjects aged over 60 years old and twenty-five young subjects aged under 30 years old were assessed by computerized dynamic posturography. Postural stability was measured in two conditions; dominant eye open and non-dominant eye open. We used the sensory organization test (SOT) for evaluating sensory impairment. A SOT assessed the subject's ability to use and integrate som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…According to Park et al, there were no significant differences between dominant vision and nondominant vision in postural control using computerized dynamic posturography in the young subjects [18]. In our research, the corrected visual acuity of the participants was better than or equal to 20/20, i.e.…”
Section: Discussioncontrasting
confidence: 39%
“…According to Park et al, there were no significant differences between dominant vision and nondominant vision in postural control using computerized dynamic posturography in the young subjects [18]. In our research, the corrected visual acuity of the participants was better than or equal to 20/20, i.e.…”
Section: Discussioncontrasting
confidence: 39%
“…The result of the present study was partially consistent with the report that kinematic changes were found depending on the blockage and opening of the visual field in the motion of reaching 21 ) and the report that the positional control was not greatly dependent on the opening of the dominant eye or the non-dominant eye in young adults 22 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Park et al 20 ) reported that the muscular activity of the gastrocnemius muscle was increased for balancing in the motion of reaching and that the lower limb muscular activity was increased when the non-dominant eye was open 22 ) . However, no significant difference was found in the present study because the results were similar between the conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Balance control is essential in all postural conditions, both static and dynamic, requiring integrity of neuromuscular system and an adequate muscle strength. Moreover, previous studies demonstrated the key role of visual inputs in achieving a steady posture control in normal subjects [ 10 , 11 ], especially in the elderly [ 12 , 13 ] and in subjects affected by neuromuscular diseases [ 14 17 ]. Furthermore, rehabilitation programs based on the recovery of visuomotor integration have been found useful in improving equilibrium [ 18 – 21 ].…”
Section: Introductionmentioning
confidence: 99%